"Remedies" Postpartum Care Center: Human Capital Strategy Planning - Rival Perdana; Rhian Indradewa; Unggul Kustiawan; Rian Adi Pamungkas (Jurnal Pendidikan Indonesia, 2025)
Human capital planning is a crucial aspect of the healthcare service industry, particularly in the postpartum care sector, which requires a workforce with high medical, psychological, and social competencies. Qualified healthcare professionals play a vital role in ensuring maternal recovery after childbirth, preventing health complications, and supporting the success of exclusive breastfeeding and infant well-being. However, challenges in human resources management in this sector remain significant, including high turnover rates among medical personnel, heavy workloads, and limited competency-based training systems. To address these challenges, a strategic and adaptive human capital planning approach is necessary to ensure a high-quality and sustainable workforce. This business plan aims to analyze the human capital planning strategy implemented by Remedies, a postpartum healthcare center, using the McKinsey 7S Model. This approach is used to evaluate the alignment of human resources strategies with the organization’s business objectives, which influence the effectiveness of workforce management. Remedies applies a short-term, medium-term, and long-term human capital strategy, focusing on enhancing medical staff competencies, strengthening organizational culture, and adopting digital technology in HR systems. In the short-term strategy, Remedies emphasizes competency-based recruitment and fundamental training for new healthcare staff. The medium-term strategy focuses on workforce skill development, professional certification, and reinforcing an empathy- and innovation-based organizational culture. Meanwhile, the long-term strategy involves the implementation of a knowledge management system, human resources digitalization, and leadership programs to prepare the future workforce. This business plan provides valuable contributions to healthcare service providers, academics, and policymakers in understanding effective human capital planning strategies to improve postpartum healthcare services. The recommendations include strengthening competency-based recruitment policies, developing incentive and employee welfare systems, and optimizing digital technology in human resources management. By implementing these strategies, healthcare organizations are expected to enhance competitiveness, reduce turnover rates, and ensure high-quality services for mothers and infants after childbirth.